Circadian Genes as Exploratory Biomarkers in DMD: Results From Both the mdx Mouse Model and Patients - Rossi, Rachele; Falzarano, Maria Sofia; Osman, Hana; Armaroli, Annarita; Scotton, Chiara; Mantuano, Paola; Boccanegra, Brigida; Cappellari, Ornella; Schwartz, Elena; Yuryev, Anton; Mercuri, Eugenio; Bertini, Enrico; et al. (Frontiers in Physiology, 2021)
Duchenne muscular dystrophy (DMD) is a rare genetic disease due to dystrophin gene mutations which cause progressive weakness and muscle wasting. Circadian rhythm coordinates biological processes with the 24-hour cycle and it plays a key role in maintaining muscle functions, both in animal models and in humans. We explored expression profiles of circadian circuit master genes both in Duchenne muscular dystrophy skeletal muscle and in its animal model, the mdx mouse. We designed a customised, mouse-specific Fluidic-Card-TaqMan-based assay (Fluid-CIRC) containing thirty-two genes related to circadian rhythm and muscle regeneration and analysed gastrocnemius and tibialis anterior muscles from both unexercised and exercised mdx mice. Based on this first analysis, we prioritised the 7 most deregulated genes in mdx mice and tested their expression in skeletal muscle biopsies from 10 Duchenne patients. We found that CSNK1E, SIRT1, and MYOG are upregulated in DMD patient biopsies, consistent with the mdx data. We also demonstrated that their proteins are detectable and measurable in the DMD patients’ plasma. We suggest that CSNK1E, SIRT1, and MYOG might represent exploratory circadian biomarkers in DMD.